Anxiety levels in victimized children who must testify in oral trials: contributions of a training program - Guerra Vio, Cristóbal; Viveros Barrera, Marcela; Calvo Lazo, Blanca; Canessa Quiroz, Pamela; Mascayano Tapia, Franco (Revista de Psicología, 2011)
There is evidence that child victims of sexual crimes, who are facing legal proceedings, may suffer secondary victimization. Several authors suggest preparing children to face this request and thus reduce the risk of secondary victimization. This article aims to describe the Anxiety levels in eight children who were trained in a program for sexually victimized children who need to testify in oral trial. We evaluated anxiety level before and immediately after the trial. There were no significant differences between the two measurements. Despite the favorable results, we consider further investigation necessary in order to evaluate program effectiveness and its ability to prevent secondary victimization. Finally, we discuss the implications of such programs in the Chilean judicial system.